Impact of Hearing Loss on the Quality of Life in Adults with Hearing Impairment - Aryal, Sajana; Bhattarai, Bebek; Prabhu, Prashanth; Bhattarai, Biraj (Nepalese Medical Journal, 2022)
Introduction: Hearing loss is the most common sensory deficit, which can impair the exchange of information. The impact of hearing loss may be profound, with consequences for the person's social, functional, and psychological well-being. This study aims to assess the overall impact of hearing loss on the quality of life in the adult population. Materials and Methods: A cross-sectional study was conducted in a tertiary care-based hospital. Patients within the age range of 18-85 years were taken. Two hundred fifty patients presenting to ENT-OPD over six months and fulfilling the inclusive criteria were recruited for the study. All patients underwent detailed audiological evaluation, including otoscopy, tympanometry, and pure tone audiometry in two room setup following ANSI standards. Communication difficulties were assessed using a modified questionnaire from the Hearing Handicap Inventory and Self-Assessment of Communication. Results: The impact of hearing loss on quality of life was associated with age, gender, and profession. The severity and type of hearing loss were significantly associated with a hearing handicap and self-reported communication difficulties. People with severe-profound hearing loss reported more handicapping conditions and communication difficulties than mild-moderate hearing loss. The impact of hearing loss was found to be more in functional and emotional aspects than physical ones. Conclusions: Hearing loss is associated with reduced quality of life. Identifying individuals with hearing loss and supplying appropriate rehabilitation with coping strategies may positively affect the quality of life for adults.